Analysis Layout of Bukit Mentik Temple in Natyasastra Perspective - Wicaksana, Ida Bagus Agung (Bali Tourism Journal, 2024)
Bukit Mentik temple has long been a significant place of worship for the local community. Some people believe that this area holds mystical power for fulfilling various desires. Many visitors come with diverse intentions, from seeking a unique vacation place to fulfilling personal wishes. The temple's architecture is distinctive and unique, reflecting Hinduism's rich cultural and spiritual heritage. The temple is built according to the Tri Mandala concept, encompassing the innermost, middle, and outer courtyards. The analysis of Bukit Mentik temple within the context of Natyasastra reveals how its architectural design and use of space play a crucial role in creating a rich and meaningful religious experience for visitors and Hindu devotees. The temple's symmetrical beauty, detailed ornamentation, and expansive open spaces used for various religious rituals and performances embody the principles of Natyasastra. These elements facilitate a profound connection between the participants and the sacred atmosphere of the temple. Additionally, the symbolic interpretations of architectural forms, such as gateways and pagodas, highlight the deep spiritual significance embedded in the temple's design. By integrating concepts from the Natyasastra and research on Balinese temple architecture, Bukit Mentik temple is a testament to the intricate relationship between religious practice, architectural beauty, and cultural heritage in Balinese Hinduism.